Simulasi Era Disrupsi dalam Iklan Apple “Crush” - Budhiman, Arief; Pandrianto, Nigar (Koneksi, 2025)
Technological progress is something that has a significant aspect of human life, one example is social media. Companies use these media to share messages with audiences. Every advertisement has a message meaning, either implicit or explicit, that it wants to convey to the audience and each audience has a different view in understanding the meaning contained in the advertisement. To find out the implied meaning in a message, help from semiotics is needed. One company that conveys interesting implied messages in advertising is Apple, which conveys the theme of change. Researchers want to examine further the meaning of the implied messages in the elements contained in the iPad Pro advertisement by carrying out semiotic analysis according to Roland Barthes through the meaning of connotation and meaning of denotation, disruption theory which discusses how change changes the order of human life, as well as assistance from the internet to strengthen the data needed to support the results of this research. Through the method used in this research, there are forms of digital representation in the Apple iPad Pro advertisement with the title "crush" which can be mentioned in three points, namely simple, addition, and revolution. Kemajuan teknologi merupakan hal yang memilki aspek signifikan terhadap kehidupan manusia, salah satu contohnya media sosial. Perusahaan menggunakan media tersebut untuk berbagi pesan kepada audiens. Setiap iklan memiliki makna pesan baik secara tersirat atau tersurat yang ingin disampaikan kepada audiens dan setiap audiens memiliki pandangan yang berbeda dalam memahamai makna yang terkandung dalam iklan, untuk mengetahui makna tersirat dalam suatu pesan diperlukannya bantuan dari semiotika. Salah satu perusahaan yang membawakan makna pesan tersirat yang menarik pada iklan adalah Apple, yang membawakan tema perubahan. Peneliti ingin menelaah lebih lanjut mengenai makna pesan tersirat pada elemen-elemen yang terkandung di dalam iklan iPad Pro dengan melakukan analisis semiotik menurut Roland Barthes melalui makna konotasi dan makna denotasi, teori disrupsi yang membahas bagaimana perubahan mengubah tatanan hidup manusia, serta bantuan dari internet untuk memperkuat data yang diperlukan agar mendukung hasil dari penelitian ini. Melalui metode yang digunakan dalam penelitian ini terdapat bentuk-bentuk representasi digital pada iklan Apple iPad Pro dengan judul “crush” yang dapat disebutkan dengan tiga poin, yaitu simpel, penambahan, serta revolusi.